2006
DOI: 10.1242/jcs.03169
|View full text |Cite
|
Sign up to set email alerts
|

Nucleo-cytoplasmic shuttling of human Kank protein accompanies intracellular translocation of β-catenin

Abstract: The human Kank protein has a role in controlling the formation of the cytoskeleton by regulating actin polymerization. Besides the cytoplasmic localization as reported before, we observed the nuclear localization of Kank in OS-RC-2 cells. To uncover the mechanism behind this phenomenon, we focused on the nuclear localization signal (NLS) and the nuclear export signal (NES). We found one NLS (NLS1) and two NESs (NES1 and NES2) in the N-terminal region of Kank-L that were absent in Kank-S, and another NLS (NLS2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…␤-Catenin can exit the nucleus via the CRM1 pathway when bound to specific partners that contain an nuclear export sequence (13)(14)(15)(16)(17). However, the major export route of ␤-catenin is independent of CRM1 (35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…␤-Catenin can exit the nucleus via the CRM1 pathway when bound to specific partners that contain an nuclear export sequence (13)(14)(15)(16)(17). However, the major export route of ␤-catenin is independent of CRM1 (35).…”
Section: Resultsmentioning
confidence: 99%
“…We and others observed that a fraction of ␤-catenin can exit the nucleus indirectly in complex with other proteins (e.g. APC, Kank, LZTS2, Axin) that do access the CRM1/exportin-1 route, at least when these proteins are overexpressed in cells (13)(14)(15)(16)(17). However, when its expression is induced transiently by Wnt signaling or chronically by cancer-linked mutations, the majority of ␤-catenin exits the nucleus independent of CRM1, exogenous soluble factors, and 18).…”
mentioning
confidence: 95%
“…KANK2 localized to podocyte cell bodies as well as nuclei in rat glomeruli ( Figure 2B and Supplemental Figure 2B). KANK proteins contain a KN motif, which includes potential nuclear localization and export signals (8), and were shown to shuttle between the nucleus and the cytoplasm via a process mediated by nuclear localization and export signals (13). KANK4 localized to podocyte cell bodies and primary processes ( Figure 2C and Supplemental Figure 2C).…”
Section: Mutations In Kank2 Cause Ns In Humansmentioning
confidence: 99%
“…As the subcellular localization of a protein is closely related to its function (Andersson et al, 2004;Chung and Eng, 2005;GamaCarvalho and Carmo-Fonseca, 2001;Gomez-Angelats and Cidlowski, 2003;Schickling et al, 2001;Wang et al, 2006;Zhan et al, 2002), we hypothesized that the NLS and NES mutants of cFLIP-L might have a different function from wild-type cFLIP-L. Cells constitutively expressing the wild-type and mutant cFLIP-L proteins (supplementary material Fig.…”
Section: Mutations In the C-terminus Of Cflip-l Abrogate The Activitymentioning
confidence: 99%